Chapter 4: Cross-Border M&As in Related and Technology-Intensive Industries: Evidence on the Dynamics of Spatial Distance, Industry Context, and Completion Likelihood of International Takeovers - Labbas, Elisa (Emerald Publishing Limited, 2019)
Many announced cross-border mergers and acquisitions (M&As) are never brought to completion despite potential negative consequences to acquirers and targets. This paper presented evidence on the dynamic effects of spatial distance and two industry-level characteristics, namely industry relatedness between the two firms and technological intensity, on the completion likelihood of cross-border M&A deals. Based on a sample of 8,489 M&A transactions we found that the completion likelihood of cross-border M&As increases with spatial distance. The effect is more pronounced for deals across technology-based industries, evidence for related deals is inconclusive.